What waiver? A qualitative exploration of awareness of the X-waiver among underserved patients and providers and the impact on tele-OUD services uptake - Adepoju, Omolola; De La Roche, Laura; Fuentes, Carlos G.; Wong, Ryan; Gilbert, Lauren (Frontiers in Psychiatry, 2025)
IntroductionThe X-waiver is a federal requirement that previously mandated healthcare providers to obtain special certification to prescribe buprenorphine for OUD. The removal of the X-Waiver represents a significant shift in U.S. drug policy aimed at expanding access to evidence-based treatment. Comparing the waiver vs. post-waiver era for telemedicine-related opioid use disorder services (TOUDS) can yield critical insights into access, utilization, and patient outcomes, particularly in underserved populations. However, a significant gap remains in the literature exploring the qualitative perspective of both providers and underserved minoritized patients. This study, part of a longitudinal study, compares provider and patient perceptions of TOUDS access in the waiver and post-waiver era.MethodsParticipants were recruited from a local OUD treatment clinic in Houston TX. We conducted in-depth qualitative interviews on eight participants, comprising of health care providers and self-identified Black and Hispanic patients. Interviews were completed in the post-X-waiver era and asked about their TOUDS experiences. Data was analyzed using reflexive thematic analysis.ResultsData analysis generated three themes: Understanding and Navigating Telemedicine for OUD treatment; Characterizing the Impacts of Distinct Forms of Stigma on TOUDS; and Waiver Awareness. Findings highlighted the benefits of TOUDS as well as barriers to uptake. Participants advocated for targeted efforts to increase public knowledge among patients and providers. They described the negative impact of stigma originating from their communities and providers. Finally, results highlighted a lack of awareness surrounding the x-waiver although, providers articulated an increase in colleague inquiries regarding how to navigate the provision of TOUDS.DiscussionTOUDS were viewed more positively by providers and patients in the post-waiver era; however, this change was not attributed to the removal of the wavier. Specifically, many patient-identified barriers prior to the removal of the X-waiver were not reported in our post-X-waiver study, and TOUDS benefits were instead emphasized. Our findings provide critical insight into the perceptions of TOUDS from both providers and patients in the post-X-waiver era that can direct policies on awareness and access.